A Case of Ruptured Aneurysm of the Accessory Middle Colic Artery - Ogoshi, Kyoji; Tajima, Tomo; Shimada, Hideo; Chino, Osamu; Morikawa, Goryu; Kenmochi, Takahiro; Kawashima, Toshifumi; Tobita, Kosuke; Sugio, Yosinori; Makuuchi, Hiroyasu (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2004)
The splenic or renal artery is a common site for intraabdominal arterial aneurysm. We report a patient with an aneurysm of the accessory middle colic artery who underwent nonemergency surgery. A 49-year-old man with upper abdominal pain and nausea was found in clinical examination to have no anemia but to have a tender mass in the left upper abdomen. Abdominal computed tomography and ultrasound examination showed a mass suspected to be an intraabdominal hematoma. An aneurysm of the accessory middle colic artery was consequently diagnosed by abdominal angiography. Intraoperative findings showed retroperitoneal hematoma on the left side of the transverse mesocolon, causing upper jejunal obstruction, necessitating left colectomy and partial jejunal resection. The postoperative course was uneventful. This is the third case report of an aneurysm of the accessory middle colic artery in the Japanese literature.